2004
DOI: 10.1063/1.1648016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bond flexibility and molecular size on the chemically selective bonding of In2O and Ga2O on GaAs(001)-c(2×8)/(2×4)

Abstract: The surface structures formed upon deposition of In2O and Ga2O by molecular beam epitaxy onto the arsenic-rich GaAs(001)-c(2 x 8)/(2 x 4) surface have been studied using scanning tunneling microscopy and density functional theory. In2O initially bonds, with indium atoms bonding to second layer gallium atoms within the trough, and proceeds to insert into or between first layer arsenic dimer pairs. In contrast, Ga2O only inserts into or between arsenic dimer pairs due to chemical site constraints. The calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In 2 O 3 ͑s͒ sublimates as In 2 O ͑g͒ and O 2 ͑g͒ at 1000-1025°C. 26 However, due to the low sticking probability of O 2 on group III-rich ͑4 ϫ 2͒ surfaces, 24 the majority of the adsorbing species is In 2 O. In the experiment, a thermocouple is used to measure the sample temperature.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2 O 3 ͑s͒ sublimates as In 2 O ͑g͒ and O 2 ͑g͒ at 1000-1025°C. 26 However, due to the low sticking probability of O 2 on group III-rich ͑4 ϫ 2͒ surfaces, 24 the majority of the adsorbing species is In 2 O. In the experiment, a thermocouple is used to measure the sample temperature.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…The bonding of In 2 O on group III-rich InGaAs͑001͒-͑4 ϫ 2͒ is quite distinct from the bonding of O 2 , In 2 O, and Ga 2 O on the As-rich GaAs͑001͒-͑2 ϫ 4͒ surfaces. 4,22,26 For O 2 chemisorption on GaAs͑001͒-͑2 ϫ 4͒, two O atoms break the As dimer bond and displace two As atoms on the row, which will create two undimerized As atoms with dangling bonds and indirectly pin the Fermi level. On the GaAs͑001͒-͑2 ϫ 4͒ surface, Ga 2 O molecules preferentially bond to As dimer rows and form Ga-As bonds.…”
Section: Oxides On Gaas Inas and Ingaas Comparisonmentioning
confidence: 99%
“…These microscopic studies ͑Hale et al 17,18 and Negoro et al 19 ͒ have given insight into the atomic structures of adsorbates bound to the GaAs͑001͒-c͑2 ϫ 8͒ / ͑2 ϫ 4͒ surface and revealed that the cause of the Fermi level pinning was not excess As on the surface.…”
Section: Introductionmentioning
confidence: 96%
“…As suggested previously, 21 the deposition of Ga 2 O on InGaAs and GaAs would ideally result in Ga 2 O units bonding to the As at the surface or on row edges. 19 This surface reaction should be difficult to detect using XPS with the As spectrum as this would manifest as As-Ga bonding at a nearly identical binding energy as that of the bulk As-Ga from the substrate.…”
mentioning
confidence: 99%